Inadequate reporting of participants eligible for randomized controlled trials – A systematic review and meta-analysis - Turjeman, Adi; Poran, Itamar; Daitch, Vered; Tau, Noam; Ayalon-Dangur, Irit; Nashashibi, Jeries; Yahav, Dafna; Paul, Mical; Leibovici, Leonard (Journal of clinical epidemiology, 2021)
•Over one third of RCTs failed to report the number of patients assessed for eligibility.•Adequate reporting of eligibility data was associated with better methodological features of trials.•Recruitment rates were significantly higher in trials sponsored by industry.•Trials should provide an accurate definition of their eligible patients to allow a better assessment of the external validity.•Adequate and transparent reporting of CONSORT flow diagram in trials will allow proper assessment of the applicability and relevance of trial findings in clinical practice. to characterize randomized controlled trials (RCTs) that did not report the overall number of participants assessed for eligibility and to identify factors associated with higher enrollment rates. Systematic review and meta-analysis of RCTs in several pre-defined fields in internal medicine. We randomly extracted 360 articles that were published in 2017. Trials that reported numbers of assessed for eligibility patients were compared with those who did not. Recruitment rates were calculated in order to investigate whether they were associated with trial characteristics. A total of 360 RCTs were included. Only 2-thirds of the trials (242/360) reported the number of patients assessed for eligibility. Trials reporting eligibility data had better methodology, reported on the tested hypothesis, included a placebo arm, evaluated soft outcomes, published their findings in higher impact journals and recruited a higher number of randomized patients than those who did not. Recruitment rates in 225 (62.5%) trials enabling their calculation, were significantly higher in trials sponsored by industry, conducted in multiple centers and countries, including inpatients, tested non-inferiority hypothesis, included a placebo arm, and evaluated surrogate outcomes. Reporting of participant eligibility continues to be scarce. Inadequate reporting was associated with poor methodological characteristics in trials.